2017
DOI: 10.1371/journal.pone.0177780
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette aerosols suppress cellular antioxidant defenses and induce significant oxidative DNA damage

Abstract: BackgroundElectronic cigarette (EC) aerosols contain unique compounds in addition to toxicants and carcinogens traditionally found in tobacco smoke. Studies are warranted to understand the public health risks of ECs.ObjectiveThe aim of this study was to determine the genotoxicity and the mechanisms induced by EC aerosol extracts on human oral and lung epithelial cells.MethodsCells were exposed to EC aerosol or mainstream smoke extracts and DNA damage was measured using the primer anchored DNA damage detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 76 publications
8
137
1
1
Order By: Relevance
“…The results of the present study agree with the findings of the previous studies that indicates the potential hazardous effects of tobacco in waterpipe and e‐cigs on oral cells. in vitro analyses suggests that aerosol from waterpipe and e‐cigs that are combined with flavoring agents has shown to enhance DNA injury and up‐regulation of a number of inflammatory proteins such as cyclooxygenase and prostaglandin E2 in gingival cells . Moreover, e‐cigs have the ability to enhance oxidative stress and generate accumulated glycation end products (AGEs) in cells of periodontal tissues .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study agree with the findings of the previous studies that indicates the potential hazardous effects of tobacco in waterpipe and e‐cigs on oral cells. in vitro analyses suggests that aerosol from waterpipe and e‐cigs that are combined with flavoring agents has shown to enhance DNA injury and up‐regulation of a number of inflammatory proteins such as cyclooxygenase and prostaglandin E2 in gingival cells . Moreover, e‐cigs have the ability to enhance oxidative stress and generate accumulated glycation end products (AGEs) in cells of periodontal tissues .…”
Section: Resultsmentioning
confidence: 99%
“…in vitro analyses suggests that aerosol from waterpipe and e-cigs that are combined with flavoring agents has shown to enhance DNA injury and up-regulation of a number of inflammatory proteins such as cyclooxygenase and prostaglandin E2 in gingival cells. 19,20 Moreover, e-cigs have the ability to enhance oxidative stress and generate accumulated glycation end products (AGEs) in cells of periodontal tissues. 21 For this reason, these pathological mechanisms may also explain the unfavorable impact of waterpipe and e-cig usage on peri-implant structures.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for the present results can be corroborated by recent results that indicate the potential hazardous effects of vaping e-cigs on oral epithelial cells and periodontal fibroblasts to e-cig vapor/aerosol with flavoring agents that enhances DNA damage and increases the expression of proinflammatory cytokines such as cyclooxygenase (COX)-2 and prostaglandin E 2 (PGE 2 ) in these cells. 21,22 Moreover, it has also been suggested that cigarette smoking and vaping e-cigs have the potential to induce oxidative stress and increases expression of advanced glycation end products (AGEs) and their receptors in cells, including gingival/periodontal tissues. 16 In this context, these mechanisms may also explain the detrimental effects of smoking tobacco and vaping on peri-implant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…So far, in vitro studies have been contradictory [52]. Several adverse effects of e-cigarette vapor or e-liquid were found in different cell lines (endothelial, epithelial and fibroblastic cells) such as increased cytotoxicity and gene expression, decreased cell viability or reduced antioxidant defenses [61][62][63][64]. Other studies have shown little or no cytotoxicity [65][66][67].…”
Section: Electronic Cigarettesmentioning
confidence: 99%